Application of host-specific bacteriophages to the surface of chicken skin leads to a reduction in recovery of Campylobacter jejuni - Atterbury, Robert J.; Connerton, Phillippa L.; Dodd, Christine E.R.; Rees, Catherine E.D.; Connerton, Ian F. (American Society for Microbiology, 2003)
Retail poultry products are widely purported as the major infection vehicle for human campylobacteriosis. Numerous intervention strategies have sought to reduce Campylobacter contamination on broiler carcasses in the abattoir. This study reports the efficacy of bacteriophage in reducing the number of recoverable Campylobacter jejuni cells on artificially contaminated chicken skin.